Mechanistic Studies of Photoinitiated Free Radical Polymerization Using a Bifunctional Thioxanthone Acetic Acid Derivative as Photoinitiator - Karasu, Feyza; Arsu, Nergis; Jockusch, Steffen; Turro, Nicholas J. (AMER CHEMICAL SOC, 2009)
A bifunctional photoinitiator for free radical polymerization, thioxanthone catechol-O,O'-diacetic acid, was synthesized, characterized, and compared to photoinitiator parameters of the monofunctional analogue, 2-(carboxymethoxy)thioxanthone. Photophysical studies such as fluorescence, phosphorescence, and laser flash photolysis in addition to photopolymerizations of methyl methacrylate show that the bifunctional photoinitiator is more efficient in polymer generation than the monofunctional derivative. These studies suggest that initiator radicals are generated from a pi-pi* triplet state in an intramolecular electron transfer, followed by proton transfer and decarboxylation to generate alkyl radicals, which initiate polymerization. The initial electron transfer is faster for the bifunctional photoinitiator than the monofunctional derivative, which is based oil laser flash photolysis studies. Because of the relatively fast intramolecular radical generation from the triplet state (triplet lifetime = 490 ns), quenching by molecular oxygen is insignificant and polymerization of methyl methacrylate proceeds efficiently without deoxygenation. At higher concentrations of initiator (similar to 5 mM) intermolecular electron transfer competes with intramolecular electron transfer. Both processes, inter- and intramolecular processes, yield initiating alkyl radicals.
Keywords: AROMATIC KETONES; CARBOXYLIC-ACIDS; QUANTUM YIELD; FLUORESCENCE; SOLVENT; PHOTOPOLYMERIZATION; DECARBOXYLATION; PHOTOPHYSICS; STATE; Polymer Science